The role of hydrilla (Hydrilla verticillata (L.f.) Royle) as soil protectant in improving soil physical, chemical, and biological properties - Dyah Roeswitawati; Zamzami Faizal Ahmad; Machmudi Machmudi (Jurnal Ilmu Pertanian, 2023)
One of the aquatic weeds inhibiting agricultural production is hydrilla. The plants are simply removed not far from the bunds to prevent them from competing with cultivated plants. However, hydrilla can be used to improve the physical, chemical, and biological properties of the soil. As an indicator of production, chili plants were planted in the trial field in Purworejo Village, Ngantang Sub-district, Malang District from October 2020 to January 2021 to test the dose of hydrilla compost. The treatments tested consisted of hydrilla compost doses of 5 t.ha⁻¹ (P₁), 10 t.ha⁻¹ (P₂), 15 t.ha⁻¹ (P₃), and 20 t.ha⁻¹ (P₄), and NPK (16:16:16) inorganic fertilizer dose of 250 kg.ha⁻¹ (P₅) as control. The experiment was arranged in a randomized block design with three replications. Analysis of variance showed no significant difference (F<0.05) in the number of flower results. Meanwhile, there was a significant effect on the number of fruits, fruit weight, and percentage of flowers into fruits (F>0.05). Hydrilla compost contained 17.3% organic C element, while the inorganic fertilizer contained 4.27%. Hydrilla compost contained decomposing microorganisms, including Pseudomonas luorescent group, Trichoderma sp., Aspergillus sp. and Penicillium sp. The optimum dose of hydrilla compost for chili plants is 20 t.ha⁻¹.